The Construction of The Teacher Against Student Religious Education in Improving The Discipline of Learning - Ahmad Khori (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
Al-Islam Tsanawiya boarding and junior high school are the educational institution that prepare its students to enroll higher education. It needs integrity and good educational environment for student to develop their creativity in involving social live, possessing ability to compete and becoming good citizenship for the nation’s future. Therefore, it is the requirements for teacher to have professional attitude and creativity as educator in improving school environment in general and teaching and learning process at classroom environment. For it is from the creative teacher having sense to seek and to find out new information the creative students will be raised. The role of school principal as motivator, supervisor and facilitator gives an enormous effect in supporting and developing the ability of the teacher to improve their services in learning and teaching process to develop learning achievement. This research uncovers the development of Islamic studies teacher in improving students’ learning discipline as the effort to improve students achievement reflected by the development of professional ability of the teacher. The purpose of this research is to grab the picture of how the development of MTs and SMP students’ discipline is carried out by the Islamic studies teacher in Bandung. This research employs case study approach; the objects of the research are viewed as a single unit. The data are collected by observation, interviews, documentary studies and purposive sample. The finding shows that the principle roles, the Islamic studies teacher as trainer, facilitator, motivator, supervisor in implementing curriculum through creativity development have the enormous effect in developing students’ achievements. It can be realistically noticed that the implementation of Islamic studies teacher development in developing students’ learning discipline in Tsanawiya boarding and junior high school in Bandung shows the improvement in teaching services through facilities and infrastructures improvement, and the quantity of prospective students improvement. The enhancement of welfare likely affects the improvement of the qualities of graduation and the acceptance of the input and outcome. The benefit of this research is this; to develop students’ achievement, it is needed the optimum development of teacher professionals in programmed and integrated way by educational stakeholder, principal, and professional organization. The writer recommends the study of technical instructions, teacher group of the same subject cluster in intensive way to produce professionals that can provide the optimum learning and teaching process for students